MANAJEMEN RANTAI PASOK PADA RANTAI PASOK BERJARING BERAS ORGANIK - Sari, Prisca Nurmala; Nurmalina, Rita (Forum Agribisnis, 2013)
For winning the competition, every entrepreneurs have to compete on supply chain. Tani Sejahtera Farm (TSF) is a distributor which cooperates with farmers in distributing organic rice in its supply chain. TSF had problems in coordinating product, financial, and information flows along its supply chain. This research aimed to analyze the condition of organic rice supply chain and its performance. The amount of samples were 14 samples which were all members of organic rice supply chain. FSCN (Food Supply Chain Networking) Framework was used for analyzing the condition of organic rice supply chain. Asset management efficiency approach was used for analyzing its performance. Organic rice supply chain had a network form. From the six elements, the condition of organic rice supply chain had not been good, especially in supply chain management, business processes and its overall performance. Supply chain management had not been implemented well in this supply chain. Its transaction system made TSF difficult to turn its capital back. From its business process, the financial and information flow had not been fluent. Its cash asset management performance had not been well also because it was too long for TSF in collecting its capital.